Enhanced biosciences revision trough gamification / Saraswathy Ramachandran and Shirley Evelynna Jayaseelan - Ramachandran, Saraswathy; Jayaseelan, Shirley Evelynna (2022)
This pilot experiment was conducted to determine the effectiveness of revision session through a gamification approach. The participants in this experiment were 118 pre-university students who took the Biosciences module in their semester 3. Students were given virtual medical case (VMC) studies for topics of hematology and virology during their revision session before the final exam. Data of the study was collected from post-item analysis for their final exam and through a questionnaire filled by the students. The experiment findings from item analysis showed significant improvement only in a few questions. Despite this, the questionnaire completed by the students has shown very positive and encouraging feedback. This clearly proves that learning through gamification is one of the most effective and useful methodologies in this current educational system. Further study is needed to determine whether incorporating gamification in other topics of this module such as bacteriology, parasitology, and immunology would have a positive impact on student motivation, engagement, and performance.